2015
DOI: 10.1016/j.jconrel.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Targeted delivery of platinum-taxane combination therapy in ovarian cancer

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 48 publications
1
40
0
Order By: Relevance
“…When BT-474 cells were treated with drug combination at a 17-AAG/PTX ratio of 4:1 in vitro , it was found that there was only 10-fold reduction in the IC 50 of PTX in combination as opposed to the 1000-fold reduction seen when the cells were treated with drugs at a 2:1 ratio and this was also reflected in less pronounced synergistic activity of drug combination (the CI value at IC 50 increased from 0.09 to 0.5, Table 5 and Table S5). This further reinforces the importance of spatial-temporal synchronization of delivery of the drugs at a defined ratio to retain synergy of action, as was reported in our previous work [53]. …”
Section: Resultssupporting
confidence: 90%
“…When BT-474 cells were treated with drug combination at a 17-AAG/PTX ratio of 4:1 in vitro , it was found that there was only 10-fold reduction in the IC 50 of PTX in combination as opposed to the 1000-fold reduction seen when the cells were treated with drugs at a 2:1 ratio and this was also reflected in less pronounced synergistic activity of drug combination (the CI value at IC 50 increased from 0.09 to 0.5, Table 5 and Table S5). This further reinforces the importance of spatial-temporal synchronization of delivery of the drugs at a defined ratio to retain synergy of action, as was reported in our previous work [53]. …”
Section: Resultssupporting
confidence: 90%
“…When the same cispaltin-loaded nanogels were also decorated with targeting ligands (e.g. folate or LHRH peptide), tumor growth inhibition could be even further enhanced [85,86,97]. Peng et al described dual pH- and temperature-responsive nanogels based on N-isopropylacrylamide, MAA, and PEG methylether methacrylate (NIPAAm-MAA-PEGMA) for the entrapment and release of cisplatin.…”
Section: Nanogels As a Therapeutic Drug Carriermentioning
confidence: 99%
“…Binary drug combination in nanogels exhibited synergistic cytotoxicity against human ovarian A2780 cancer cells and exerted a superior antitumor activity in cancer xenograft models in vivo as compared to individual drug-loaded nanogels or free drugs. The benefits of synchronized co-delivery of the platinum-taxane drug combination via single carrier can be further enhanced by targeting nanogels to folate receptor, which are overexpressed in most ovarian cancers [97]. In another study, we reported an efficient co-encapsulation of DOX and 17-allylaminodemethoxygeldanamycin (17-AAG) into PEG-PGlu nanogels with multiple hydrophobic domains that are located within the crosslinked polyion PGlu core [83].…”
Section: Nanogels As a Therapeutic Drug Carriermentioning
confidence: 99%
“…Many advantages of polymeric micelles for cancer therapy have been reported, including reduced toxicity, remarkable biocompatibility, controllable drug release and prolonged circulation time . In addition, polymeric micelles tend to accumulate in tumor tissues owing to the enhanced permeability and retention (EPR) effect . Nevertheless, the passive targeted efficiency of the EPR effect is insufficient to achieve a high enough concentration of drug in malignant tumor tissues.…”
Section: Introductionmentioning
confidence: 99%
“…However, in normal organs and tissues, FRα is expressed merely on the luminal surface of polarized epithelia of a few locations, such as the kidney and lungs, and FRβ is mainly expressed in the placenta and in white blood cells of myeloid lineage . In contrast, FRα is over‐expressed on the surface of various neoplastic cells, including brain, ovarian, kidney, lung, pancreatic, endometrial, colorectal, testicular, gastric, prostate, bladder, breast, and head and neck cancer cells, on account of the high rates of cell division and the increased requirement for FA . As a consequence, drug carriers modified with FA exhibit high levels of cell uptake efficiency by FR‐over‐expressing tumor cells.…”
Section: Introductionmentioning
confidence: 99%